Comparing Dimensional Models Assessing Personality Traits and Personality Pathology Among Adult ADHD and Borderline Personality Disorder. (August 2016) - Koerting, Johanna; Pukrop, Ralf; Klein, Philipp; Ritter, Kathrin; Knowles, Mark; Banzhaf, Anke; Gentschow, Laura; Vater, Aline; Heuser, Isabella; Colla, Michael; Roepke, Stefan
Objective: This pilot study was a comparison of dimensional models assessing personality traits and personality pathology in a clinical sample of adults diagnosed with ADHD and adults diagnosed with borderline personality disorder (BPD), and a nonclinical control sample of healthy adults.Method: Personality traits were assessed using the NEO–Personality Inventory–Revised (NEO-PI-R) and dimensional personality pathology with the Dimensional Assessment of Personality Pathology–Basic Questionnaire (DAPP-BQ).Results: Adults with ADHD and BPD produced higher Emotional Dysregulation/Neuroticism and Dissocial Behavior scores than controls. For the Extraversion/Inhibitedness scale, adults with BPD produced significantly lower scores than adults with ADHD and controls. On the Conscientiousness/Compulsivity domains, Conscientiousness scores were lower for both disorders, whereas low Compulsivity values were specific to adult ADHD.Conclusion: Our results suggest that patients with adult ADHD and BPD have distinguishable profiles of personality traits and personality pathology.